Analisis Penerapan Warehouse Management System terhadap Efisiensi Pengelolaan Gudang - Andi Nurul Ma’rifa; Andi Muhammad Rivai; Febhisatria, Andi; Annisa Dwifitri, Syifa; Multifasari, Lilis (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the impact of implementing a Warehouse Management System (WMS) on warehouse management efficiency in the context of modern supply chain management. The background of the problem is based on the operational inefficiencies of traditional warehouses, which are characterized by time-consuming manual processes, high material handling costs, and susceptibility to human error. The results of the analysis show that WMS, which is a database-based computer application system that automates the entire warehousing process (from receiving to shipping), can substantially improve operational efficiency, including speeding up lead time, increasing stock accuracy (up to 98%), and reducing the defect ratio. The success of WMS implementation is largely determined by three main pillars: System Quality, Information Quality (real-time accuracy), and Service Quality (human resource training). However, the risk of failure remains, especially from human error and technical network constraints. In conclusion, WMS is not just a transactional tool, but a strategic intelligent system that must be integrated with advanced technologies such as IoT, AI, and Data Analytics to achieve superior inventory management, near-perfect data accuracy, and meet the demands of e-commerce/omnichannel businesses that require high speed. Keywords: Inventory Accuracy; Warehouse Efficiency; Human Error; Supply Chain Management; Warehouse Management System (WMS)